Avaliação do uso de SOF (Fluido De Oviduto Sintético) e CLA (Ácido Linoleico Conjugado) na expressão gênica de genes relacionados ao metabolismo lipídico e maturação oocitária em COCs (Complexos Cumulus-Oócito) bovinos - Mendes, Adriano Felipe (2019)
In order to develop a medium capable of supporting all stages of in vitro production of bovine embryos, the aim of this study was to investigate whether the use of synthetic oviduct fluid (SOF) with or without conjugated linoleic acid (CLA) during in vitro maturation of bovine oocytes changes the abundance of transcripts linked to lipid metabolism and oocyte maturation. Cumulus-oocyte complexes (COCs) were aspirated from slaughtered ovaries and matured into four groups: M199 (Medium 199), M199+CLA (M199 with 100 µM CLA), SOF and SOF+CLA (SOF with 100 µM CLA). The relative abundance of oocytes and cumulus cells mRNA was evaluated after maturation. Total mRNA samples were treated with DNAse before being subjected to the reverse transcription protocol. RT-qPCR analyzes of the FADS2 (fatty acid desaturase 2), SCD1 (stearoyl-CoA desaturase 1), SREBP1 (sterol regulatory element binding transcription factor 1), GREM1 (gremlin 1), AREG (amphiregulin) and COX2 (cyclooxygenase 2) genes were performed. The gene PPIA (peptidylprolyl isomerase A) was used as reference and the ΔΔCt method with efficiency correction was used to calculate the relative expression values (target genes/PPIA) for each target gene using a control sample and calibrator. The samples were distributed in a completely randomized design in a 2x2 factorial scheme, totaling 4 treatments with 5 replications. Data were subjected to analysis of variance and in case of significant difference (p<0.05) the means were compared by Tukey test at 5% significance. The use of the SOF medium in the maturation of bovine COCs results in higher relative mRNA abundance of quality markers GREM1 (p=0.0065) and COX2 (p=0.0040) in oocytes and GREM1 (p=0.0004) in cumulus cells. In addition, the SOF medium provides higher relative abundance of FADS2 (p=0.0001), essential for lipid metabolism, in oocytes. Additionally, oocytes matured in SOF medium show lower relative abundance of SCD1 without influence of CLA addition. In contrast, the relative abundance of SCD1 is reduced in M199 medium using CLA. We conclude that the SOF medium provides greater abundance of oocyte quality markers regardless of the addition of CLA.